2014
DOI: 10.1051/0004-6361/201423546
|View full text |Cite
|
Sign up to set email alerts
|

Processing of analogues of plume fallout in cold regions of Enceladus by energetic electrons

Abstract: Context. Enceladus, a small icy moon of Saturn, is one of the most remarkable bodies in the solar system. This moon is a geologically active object, and despite the lower temperatures on most of its surface, the geothermally heated south polar region presents geysers that spouts a plume made of water (∼90%), carbon dioxide, methane, ammonia, and methanol, among other molecules. Most of the upward-moving particles do not have the velocity to escape from the gravitational influence of the moon and fall back to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 33 publications
(55 reference statements)
0
16
0
Order By: Relevance
“…The production of OCN À is very enhanced at 80 K. Pilling and Bergantini 10 also reported this dependence of the OCN À production with temperature in another experiments also employing so X-rays in astrophysical related ices. Bergantini et al 43 have presented several sets of electroninduced chemistry of similar ices containing initially H 2 O, CO 2 , NH 3 and CH 4 . The reaction routes are able to describe the formation of daughter species such as OCN À , NH, CH 3 OH, HCONH 2 , and others.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of OCN À is very enhanced at 80 K. Pilling and Bergantini 10 also reported this dependence of the OCN À production with temperature in another experiments also employing so X-rays in astrophysical related ices. Bergantini et al 43 have presented several sets of electroninduced chemistry of similar ices containing initially H 2 O, CO 2 , NH 3 and CH 4 . The reaction routes are able to describe the formation of daughter species such as OCN À , NH, CH 3 OH, HCONH 2 , and others.…”
Section: Resultsmentioning
confidence: 99%
“…Bergantini et al, 43 also employing infrared spectroscopy have studied similar ice mixture at 20 K, in the presence of ionizing 1 keV electron beam. From their data (Fig.…”
Section: Timescale To Reach Chemical Equilibriummentioning
confidence: 99%
See 1 more Smart Citation
“…Such fast primary electrons lose energy by creating electron-hole pairs at a distance that is generally short compared with the penetration depth L of the incoming photon. As indicated by Bergantini et al (2014b), the range of 1 keV electrons is around 60 nm inside such astrophysical analog samples and for low-energy electrons (∼ 5 eV), the mean-free path inside such ices is around 1-2 nm; ii) Excitation of secondary electrons by fast primary electrons (photoelectrons). Once a secondary electron is created, it will undergo a short random walk in the material while losing energy due to the creation of phonons.…”
Section: X-ray Induced Processes In Icesmentioning
confidence: 97%
“…On the other hand, previous studies have shown that processing of various ice mixtures by UV photons (Bernstein et al 1995;Henderson & Gudipati 2015), energetic electrons (Jones et al 2011;Bergantini et al 2014;Henderson & Gudipati 2015), and ions (Gerakines et al 2004;Demyk et al 1998) produce both formamide and isocyanic acid. The experimental results obtained so far are discussed in some detail in Sect.…”
Section: Introductionmentioning
confidence: 95%